PENGARUH KEBIJAKAN PENDIDIKAN JASMANI TERINTEGRASI TERHADAP GAYA HIDUP SEHAT DI KALANGAN SISWA SEKOLAH DASAR - Dini Permata Sari; Tito Parta Wibowo; Pardiman; Elsa Zahra; Refly Jayadi Ningrat; Ahmad Septiana; Pajri Sumardi; Ahmad Firdaus; Anshori; Panji Gumelar (CV. Denasya Smart Publisher, 2025)
An integrated physical education policy was a strategic approach in shaping a healthy lifestyle from an early age. This study aimed to determine the effect of the integrated physical education policy implementation on the healthy lifestyle of elementary school students. The method used was descriptive quantitative with a survey approach. The sample consisted of 120 students from four elementary schools that had implemented the policy in X city. The results showed a significant positive correlation between the implementation of the integrated physical education policy and the improvement of students' healthy living behaviors, which included regular physical activity, a balanced diet, and awareness of personal hygiene and health. This policy proved effective in instilling healthy living values through structured physical activities and supporting the strengthening of character education